Base‐Catalyzed Intramolecular 5‐exo‐dig Cyclization of 2‐Propynyl‐1, 3‐dicarbonyl Compounds: An Atom‐Economic Route to Stereodefined 2‐Methylene‐2, 3‐dihydrofurans. Issue 23 (7th July 2014) - Ma, Quan; Wang, Yeming; Zhao, Yuegang; Liao, Peiqiu; Sun, Bo; Bi, Xihe
Abstract: A new and straightforward base‐catalyzed 5‐ exo ‐ trig cyclization of 2‐propynyl‐1, 3‐dicarbonyl compounds leads to the corresponding stereodefined 2‐methylene‐2, 3‐dihydrofurans in excellent yields. Abstract : A regio‐ and stereoselective 5‐ exo ‐ dig cyclization of 2‐propynyl‐1, 3‐dicarbonyl compounds under metal‐free conditions has been developed. This reaction constitutes a new and straightforward method for the efficient synthesis of stereodefined 2‐methylene‐2, 3‐dihydrofurans. Spiro‐dihydrofurans can also be prepared in excellent yields by this approach.